INTERESTING LESSON AND SOME EFFECTIVE METHODS OF WORKING IN THE CLASSROOM - Irgesheva Nasibaxon Dadajanovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Remember to adapt these strategies to the specific needs, proficiency levels, and interests of your learners. Continuously seek feedback from your students to gauge their engagement and make adjustments to your teaching methods as needed. By creating a dynamic, learner-centered classroom environment, you can make language learning enjoyable, meaningful, and effective.